Peripheral Mononuclear Cell Resistin mRNA Expression Is Increased in Type 2 Diabetic Women - Panayoula C. Tsiotra; Constantine Tsigos; Eleni Anastasiou; Eleni Yfanti; Eleni Boutati; Emmanouil Souvatzoglou; Ioannis Kyrou; Sotirios A. Raptis (Mediators of Inflammation)
Resistin has been shown to cause insulin resistance and to impair glucose tolerance in rodents, but in humans its physiological role still remains elusive. The aim of this study was to examine whether resistin mRNA expression in human peripheral mononuclear cells (PBMCs) and its corresponding plasma levels are altered in type 2 diabetes. Resistin mRNA levels were easily detectable in human PBMC, and found to be higher in DM2 compared to healthy women (P=.05). Similarly, mononuclear mRNA levels of the proinflammatory cytokines IL-1β, TNF-α, and IL-6 were all significantly higher in DM2 compared to control women (P<.001). The corresponding plasma resistin levels were slightly, but not significantly, increased in DM2 women (P=.051), and overall, they correlated significantly with BMI (r=0.406, P=.010) and waist circumference (r=0.516, P=.003), but not with fasting insulin levels or HOMA-IR. Resistin mRNA expression is increased in PBMC from DM2 women, together with increased expression of the inflammatory cytokines IL-1β, TNF-α, and IL-6, independent of obesity. These results suggest that resistin and cytokines might contribute to the low-grade inflammation and the increased atherogenic risk observed in these patients.